The Impact of Humble Leadership on Enhancing Organizational Commitment: A Field Study of Employees in the Emirate of Jazan Region - Laghabi, Mohammed Yahya; Alariki, Baseim Qaid (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to identify the levels of both modest control and organizational commitment in the Emirate of Jazan Region, as well as to contribute to modest control in improving organizational commitment among employees in the Emirate of Jazan Region, through an applied study based on descriptive and analytical roles. The study population represented all employees in the Emirate of Jazan Region, numbering (509) individuals. The study tool (questionnaire) was applied to a sample of (217) employees in the Emirate of Jazan Region. The study differs in its modest dynamics (self-awareness, suitability for learning, differs from each other, self-difference), and is effective in organizational implementation. Given the vast diversity of variables (self-awareness, seriousness in learning, appreciation of others, and self-change) in the Emirate of Jazan Region from the perspective of employees, where it was very high, with an overall average of 4.21 and a global deviation of 0.89, the overall level of organizational performance in the Emirate of Jazan Region from the perspective of employees was high, with an overall average of 4.12 and an acceptable deviation of 1.03. Furthermore, there were no statistically significant results at the significance level (α ≥ 0.05) regarding the effect of humble leadership on organizational performance, nor were there any statistically significant differences at the significance level (α ≥ 0.05) in the study’s study on the role of humble leadership in organizational commitment in the Emirate of Jazan Region attributed to the gender variable, with a significance level of 0.458. There were statistically significant differences at the significance level (α ≥ 0.05) in the research on the role of humble leadership in improving organizational performance in the Emirate of Jazan Region, attributed to the educational level variable. This main difference stems from postgraduate studies, with the significance level reaching (0.012).